CLINICAL AND BIOCHEMICAL CHARACTERISTICS AT THE CIRRHOSIS OF VARIOUS GENESIS - A. R. Bilalova; V. V. Makashova; G. A. Shipullin (SINAPS LLC, 2016)
Purpose of the study. To carry out a comparative description of the clinical and biochemical parameters at patients with cirrhosis of an alcoholic genesis (CP-HGA) and cirrhosis of mixed etiologies - CP-HGM (HСV+ alcohol).Materials and methods. The study involved 62 patients with cirrhosis of different etiologies, who carries out clinical, immunogenetic and biochemical studies.Results. Patients with the 3d genotype and low viral load were registered with cirrhosis of mixed etiologies (HСV+ alcohol). At the cirrhosis Class B for Child-Pugh basic data biochemical parameters were similar in patients with CP-HGA and CP-HGM, but ALT and AST activity, which are significantly higher than observed in patients with CP-HGM. At dismissal, ALT and GGT activities were detected significantly higher in patients with CP-HGM than the CP-HGA. At the cirrhosis Class C for Child-Pugh the baseline, reflecting cholestasis - is total bilirubin, GGT and alkaline phosphatase and were detected significantly higher in the CP-HGA, than with CP-HGM significantly reduced, and thore is no differences between the groups to be discharged from the hospital, in addition to the activity of GGT, which it remained significantly higher in the CP-HGA, than with CP-HGM. Cytolytic activity of enzymes (ALT, AST) during the entire period of the disease was observed significantly higher normal values and did not depend on the CP etiology.Conclusion decision. The maximum rate of change of the basic biochemical parameters is observed in patients with cirrhosis of mixed etiologies Class B for Child-Pugh and at the cirrhosis of an alcoholic genesis - in patients with cirrhosis Class C.